Bringing the rain to Kapiti Plain : a Nandi tale - Aardema, Verna; Vidal, Beatriz (New York : Puffin Books, 1983)
A cumulative rhyme relating how Ki-pat brought rain to the drought-stricken Kapiti Plain.
Keywords: Droughts -- Fiction; Stories in rhyme; Africa -- Fiction